Birds build camouflaged nests. (1st October 2014) - Bailey, Ida E.; Muth, Felicity; Morgan, Kate; Meddle, Simone L.; Healy, Susan D.
Abstract: It is assumed that many birds attempt to conceal their nests by using camouflage. To our knowledge, however, no previous experimental studies have explicitly tested this assumption. To explore whether birds choose materials that match the background colors of nest sites to reduce the conspicuousness of their nests, we offered nest-building male Zebra Finches ( Taeniopygia guttata ) a choice of nest materials that either matched or did not match the color of their nest cup and the surrounding cage walls. Males chose to nest predominantly with material that matched the background color of the cage. To our knowledge, this is the first experimental evidence that birds actively select materials that camouflage their nests.